Profile of Tumor Necrosis Factor Alpha Levels in Childhood Malignancy with Febrile Neutropenia - Tigor Pandapotan Sianturi; Puspa Wardhani; I Dewa Gede Ugrasena (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Infection is a significant cause of morbidity and mortality in childhood malignancy with Febrile Neutropenia (FN). Tumor Necrosis Factor-Alpha (TNF-Î±) is involved in host defense against bacterial invasion. However, changes in TNF-Î± levels with the possibility of bacterial infection confirmed by blood culture are still unclear. The study aimed to evaluate TNF-Î± levels in childhood malignancy with FN who had blood cultures with a control group. Observational cross-sectional analysis during January-October 2020 at Dr. Soetomo General Academic Hospital, Surabaya. Childhood malignancy with FN episodes as the case group and nonfebrile neutropenia as the control. TNF-Î± levels examination used plasma with the Enzyme-Linked Immunosorbent Assay (ELISA) sandwich method. Blood culture results were obtained from the patient's medical record. The differences in TNF-Î± levels in the case groups and control were analyzed by the T-square test for two independent samples or Mann-Whitney U according to the data distribution. There were 18 cases group with 30 FN episodes and 15 controls. There were 8(26.66%) positive and 22(73.33%) negative blood cultures from 30 FN episodes. The mean TNF-Î± levels in the positive blood culture cases group and control: 14.72±5.77 and 9.78±2.74 pg/mL, and the median (min-max) negative blood cultures: 12.19 (7.01-25.70) pg/mL. There was no significant difference in TNF-Î± levels in the positive and negative blood culture cases group (p=0.527), but there was a significant difference in the control (p=0.049 and p=0.027). Therefore, TNF-Î± levels cannot be used as a marker of bacterial infection in the case groups.